High proportion mesoporous disordered porous carbon material and three-stage preparation method thereof

CN122977378APending Publication Date: 2026-10-27FUJIAN XINSEN CARBON +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611433724.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但该方法孔径分布极宽,同时包含大量微孔与大介孔,中介孔占比低,无法实现中介孔率>70%的精准调控,难以适配特定尺寸的吸附质或离子

Benefits of technology

[0024]1、本发明采用逆向调控思路,先制备宽孔径分布的超高孔容基体,再通过压缩大介孔和扩大微孔的双向调节,使孔道向2~10nm的中介孔区间收敛,在无模板条件下同时实现总孔容≥0.5cm³/g与中介孔率>70%,解决了现有技术中高孔容必然伴随微孔主导的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977378A_ABST
    Figure CN122977378A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of carbon material preparation, and discloses a high-proportion mesoporous disordered porous carbon material and a three-stage preparation method thereof. In the method, carbon-containing precursor powder and a chemical foaming agent are carbonized at high temperature to prepare an ultra-high-pore-volume foamed carbon matrix, the matrix is vacuum-impregnated with a liquid carbon solution as a thickening agent, and after drying, secondary carbonization is carried out, carbon deposition is performed on the pore wall to shrink large mesopores; and finally, slight activation is performed in an oxidizing atmosphere to preferentially expand micropores to the mesopore interval. The application is based on bidirectional regulation of capillary selective deposition and curvature selective activation, does not need a template, and the obtained material has a three-dimensional connected disordered pore structure, the total pore volume is greater than or equal to 0.5 cm3 / g, the mesopore pore volume proportion in the range of 2-10 nm is greater than 70%, the micropore (less than 2 nm) proportion is less than 25%, and the large mesopore (10-50 nm) proportion is less than 5%. The process is low in raw material cost, simple in process flow, green and low in waste, is suitable for various precursors such as agricultural and forestry waste and resin, and is excellent in mass transfer performance of the product, and can be used in the fields of porous carbon for negative electrode materials, VOCs adsorption and catalytic carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon material preparation technology, specifically to a high-proportion mesoporous disordered porous carbon material and its three-stage preparation method. Background Technology

[0002] Porous carbon materials are widely used in supercapacitor electrodes, lithium-sulfur battery hosts, ion battery anodes, VOCs adsorption, wastewater treatment, and catalyst supports due to their high specific surface area, good chemical stability, and excellent conductivity. Pore structure is the core factor determining the performance of porous carbon applications. Mesopores of 2–10 nm can match the sizes of most electrolyte ions and organic molecules, possessing both high adsorption capacity and rapid mass transfer capability, making them a current research focus for porous carbon materials.

[0003] Existing methods for preparing mesoporous carbon can be mainly divided into three categories, all of which have obvious technical limitations:

[0004] 1. Hard template method: Using mesoporous silicon such as SBA-15 and KIT-6 as templates, carbon precursors are filled, followed by carbonization and etching to remove the template, resulting in a regular and ordered mesoporous structure. However, this process is complex, the template agent is expensive, the etching process generates a large amount of acid and alkali waste liquid, and the total pore volume of the product is usually less than 0.4 cm³ / g, resulting in low production efficiency and difficulty in scaling up.

[0005] 2. Chemical activation method: Using KOH, H3PO4, ZnCl2, etc. as activators, the carbon precursor is mixed and activated at high temperature to prepare porous carbon with high specific surface area and high pore volume. However, this method mainly creates micropores, and the microporosity of the product is usually higher than 70%, while the mesopore ratio is difficult to exceed 30%, which cannot meet the application scenarios with high requirements for the proportion of mesopores.

[0006] 3. Physical foaming method: Using ammonium bicarbonate, urea, ammonium carbonate, etc. as chemical foaming agents, these are blended with carbon precursors and then carbonized at high temperature. The foaming agent decomposes to generate gas and create pores, resulting in disordered porous carbon with a total pore volume of over 1.5 cm³ / g. However, this method has an extremely wide pore size distribution, containing a large number of micropores and mesopores, with a low proportion of mesopores. It cannot achieve precise control of the mesopore rate (>70%), making it difficult to adapt to adsorbates or ions of specific sizes.

[0007] In summary, existing technologies cannot simultaneously achieve high total pore volume and a high proportion of mesopores in porous carbon without templates and at low cost, presenting a technical contradiction of "difficulty in achieving both high pore volume and narrow pore size distribution." Therefore, there is an urgent need to develop a simple, cost-controllable, and precisely adjustable method for preparing porous carbon with a high proportion of mesopores. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a high-proportion mesoporous disordered porous carbon material and its three-stage preparation method, which can effectively solve the above-mentioned technical problems.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] A three-stage preparation method for a high-proportion mesoporous disordered porous carbon material includes the following steps:

[0011] Step 1: Preparation of ultra-high pore volume foamed carbon matrix: The carbon precursor powder and chemical foaming agent are mixed evenly at a mass ratio of 100:5-30. The mixture is heated to 600-900℃ under an inert atmosphere for carbonization. After holding at this temperature for 10-120 minutes, it is cooled to obtain a foamed carbon matrix with a total pore volume of 1.5-2.8 cm³ / g.

[0012] Step 2: Directional pore wall compression and densification: Prepare a liquid carbon precursor solution as a pore wall thickening agent. Impregnate the foamed carbon matrix obtained in Step 1 in the pore wall thickening agent. The impregnation conditions are: impregnation time 1 to 120 minutes, vacuum degree 0 to -0.1 MPa to allow the thickening agent to penetrate into the macropores and mesopores. After removal, dry in an environment with a drying and curing temperature of 90 to 150°C. Then, perform secondary carbonization at 1500 to 1800°C under an inert atmosphere and keep warm for 0.5 to 3 hours. After carbonization, the thickening agent is deposited on the inner wall of the pores, reducing the pore size of macropores and mesopores.

[0013] Step 3: Mild activation and directional pore expansion: The carbonized product obtained in Step 2 is placed in an oxidizing atmosphere and mildly activated at 700-900℃ for 300-650 minutes. After cooling, a high proportion of disordered porous carbon material with mesopores is obtained.

[0014] Furthermore, the carbon-containing precursor powder mentioned in step one is selected from one or more of coconut shell charcoal, walnut shell charcoal, urea-formaldehyde resin, phenolic resin, melamine-urea-formaldehyde resin, sucrose, and starch; the chemical foaming agent is selected from one or more of ammonium bicarbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, and urea.

[0015] Furthermore, the carbon-containing precursor powder mentioned in step one is biomass fruit shell micro powder with a mesh size of 500-1000 mesh and a water absorption rate of >50%; the chemical foaming agent is potassium bicarbonate, and its addition amount is 10-20% of the mass of the carbon-containing precursor powder.

[0016] Furthermore, the heating rate in step one is 2–20 °C / min; the inert atmosphere is one of nitrogen, argon, or helium.

[0017] Furthermore, the pore wall thickening agent mentioned in step two is a liquid carbon precursor solution with a mass fraction of 5-35%, wherein the liquid carbon precursor solution is selected from one of sucrose aqueous solution, glucose aqueous solution, furfuryl alcohol ethanol solution, and phenolic resin ethanol solution.

[0018] Furthermore, the pore wall thickening agent is a sucrose aqueous solution with a mass fraction of 10-20%.

[0019] Furthermore, the impregnation conditions in step two are: impregnation time 20 to 60 minutes, vacuum degree -0.02 to -0.08 MPa.

[0020] Furthermore, the oxidizing atmosphere mentioned in step three is one of carbon dioxide, water vapor, or oxygen.

[0021] Furthermore, in step three, the activation time is 300–500 minutes, and the pore enlargement factor of the micropores is controlled at 1.5–3 times.

[0022] A high-proportion mesoporous disordered porous carbon material is prepared by the above-mentioned three-stage preparation method. The porous carbon material has a three-dimensional interconnected disordered pore structure with a total pore volume ≥ 0.5 cm³ / g. In terms of pore volume ratio, the proportion of mesopores with a pore size of 2-10 nm is > 70%, the proportion of micropores with a pore size of less than 2 nm is < 25%, and the proportion of macropores with a pore size of 10-50 nm is < 5%.

[0023] This invention provides a high-proportion mesoporous disordered porous carbon material and its three-stage preparation method. It has the following beneficial effects:

[0024] 1. This invention adopts a reverse control approach, first preparing an ultra-high porosity matrix with a wide pore size distribution, and then using bidirectional adjustment of compressing large mesopores and expanding micropores to make the pores converge into the mesopore range of 2-10nm. Under template-free conditions, it simultaneously achieves a total pore volume ≥0.5cm³ / g and a mesopore rate >70%, solving the technical bottleneck in the prior art where high pore volume is inevitably accompanied by micropore dominance.

[0025] 2. This invention does not require expensive mesoporous template agents and precision molding equipment. Production can be completed using only conventional mixing equipment, carbonization furnaces, impregnation tanks, and activation furnaces. The process is short and easy to operate, making it suitable for large-scale industrial production. Furthermore, this invention can use agricultural and forestry waste-based carbon such as coconut shells and walnut shells as carbon precursors. The foaming agent and thickening agent are both inexpensive and readily available chemical raw materials. The production process does not generate highly toxic reagents or large amounts of hazardous waste, meeting the requirements of green manufacturing.

[0026] 3. The porous carbon obtained in this invention possesses three-dimensionally interconnected disordered channels, with a high proportion of mesopores and concentrated pore size. This results in rapid adsorption rates and high capacity for large-sized ions and organic molecules, while exhibiting low mass transfer resistance. When applied to supercapacitors, it can be matched with organic electrolytes and ionic liquids to achieve high specific capacitance and high rate performance. When applied to lithium-sulfur batteries, it can physically confine polysulfides, suppressing the shuttle effect. It is also suitable for use in sodium / potassium ion battery anodes, VOCs adsorption, catalyst supports, and other fields. Attached Figure Description

[0027] Figure 1 The image shows the interconnected hole structure of the material obtained in Example 1 under a scanning electron microscope.

[0028] Figure 2 This is a scanning electron microscope image of the material obtained in this invention;

[0029] Figure 3 This is another electron microscope scan of the material obtained in this invention. Detailed Implementation

[0030] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0031] Example 1

[0032] Weigh 100g of coconut shell powder (600 mesh, water absorption rate 50.2%) and 15g of ammonium bicarbonate, mix them evenly in a mixer, and transfer them to a tube furnace; under a nitrogen atmosphere, heat the mixture to 750℃ at a heating rate of 15℃ / min, hold it at that temperature for 30 minutes, and then let it cool naturally to room temperature to obtain a foamed carbon matrix.

[0033] Prepare a 15% (w / w) sucrose aqueous solution as a pore wall thickening agent; place the foamed carbon matrix into a vacuum impregnation tank, evacuate to -0.05 MPa, inject the thickening agent until the material is completely submerged, and keep impregnated for 30 minutes; after releasing the vacuum, take out the material, drain the surface solution, and place it in an oven at 120°C for 2 hours.

[0034] The dried material was transferred to a graphite furnace and heated to 1600°C at a rate of 10°C / min under a nitrogen atmosphere. The temperature was maintained for 1 hour for secondary carbonization, and the intermediate was obtained after natural cooling.

[0035] The intermediate was placed in a tube furnace and carbon dioxide containing 2% O2 was introduced at a flow rate of 120 mL / min. The temperature was increased to 800 °C at a rate of 10 °C / min and activated for 350 minutes. The material was then naturally cooled to room temperature to obtain the final high-proportion mesoporous disordered porous carbon material.

[0036] Example 2

[0037] Weigh 100g of walnut shell powder (800 mesh, water absorption rate 60.5%) and mix it evenly with 12g of ammonium carbonate. Place the mixture in a tube furnace and heat it to 800℃ at 20℃ / min under a nitrogen atmosphere. Hold the temperature for 20 minutes and allow it to cool naturally to obtain a foamed carbon matrix.

[0038] A 12% glucose aqueous solution was prepared as a pore wall thickening agent, and the foamed carbon matrix was impregnated under normal pressure for 15 minutes; after being removed and drained, it was dried at 120℃ for 2 hours.

[0039] The dried material was transferred to a graphite furnace and heated to 1600°C at a rate of 10°C / min under a nitrogen atmosphere. The temperature was maintained for 1 hour for secondary carbonization, and the intermediate was obtained after natural cooling.

[0040] The intermediate was placed in a tube furnace and carbon dioxide containing 2% O2 was introduced at a flow rate of 120 mL / min. The temperature was increased to 800 °C at a rate of 10 °C / min and activated for 350 minutes. The material was then naturally cooled to room temperature to obtain the final high-proportion mesoporous disordered porous carbon material.

[0041] Example 3

[0042] Weigh 80g of phenolic resin powder (average particle size 30μm) and mix it evenly with 10g of ammonium bicarbonate. Place the mixture in a tube furnace and heat it to 850℃ at 10℃ / min under a nitrogen atmosphere. Hold the temperature for 15 minutes and allow it to cool naturally to obtain a foamed carbon matrix.

[0043] A 20% (w / w) furfuryl alcohol-ethanol solution was prepared as a pore wall thickening agent, and the foamed carbon matrix was immersed in it under a vacuum of -0.03 MPa for 45 minutes; after being removed and drained, it was dried at 120°C for 2 hours.

[0044] The dried material was carbonized at 1600℃ for 1 hour under a nitrogen atmosphere to obtain an intermediate.

[0045] The intermediate was placed in a tube furnace, steam was introduced, and the temperature was raised to 900℃ for activation for 300 minutes; after natural cooling, the final porous carbon material was obtained.

[0046] Comparative Example 1

[0047] Weigh 100g of coconut shell powder (600 mesh, water absorption rate 50.2%) and 15g of ammonium bicarbonate, mix them evenly in a mixer, and transfer them to a tube furnace; under a nitrogen atmosphere, heat the mixture to 750℃ at a heating rate of 15℃ / min, hold it at that temperature for 30 minutes, and then let it cool naturally to room temperature to obtain a foamed carbon matrix.

[0048] The foamed carbon matrix was placed in a tube furnace, and carbon dioxide containing 2% O2 was introduced at a gas flow rate of 120 mL / min. The temperature was increased to 800℃ at a rate of 10℃ / min and activated for 350 minutes. The material was then naturally cooled to room temperature to obtain the control sample carbon material.

[0049] Comparative Example 2

[0050] Weigh 100g of coconut shell powder (600 mesh, water absorption rate 50.2%) and 15g of ammonium bicarbonate, mix them evenly in a mixer, and transfer them to a tube furnace; under a nitrogen atmosphere, heat the mixture to 750℃ at a heating rate of 15℃ / min, hold it at that temperature for 30 minutes, and then let it cool naturally to room temperature to obtain a foamed carbon matrix.

[0051] Prepare a 15% sucrose aqueous solution as a pore wall thickening agent; place the foamed carbon matrix A into a vacuum impregnation tank, evacuate to -0.05 MPa, inject the thickening agent until the material is completely submerged, and keep impregnated for 30 minutes; after releasing the vacuum, take out the material, drain the surface solution, and place it in an oven at 120℃ for 2 hours.

[0052] The dried material was transferred to a tube furnace and heated to 1600℃ at 10℃ / min under a nitrogen atmosphere. It was then held at this temperature for 1 hour for secondary carbonization. After natural cooling, the control sample carbon material was obtained without further activation treatment.

[0053] The materials prepared in Examples 1-3 and Comparative Examples 1-2 were all characterized using the DFT model in the gas adsorption BET method: the total pore volume was taken as the total pore volume at a relative pressure of 0.99, and the microporosity, mesoporosity, and macroporosity were the volume ratios of the pore volume to the total pore volume for the corresponding pore size range. The experimental data are recorded in Table 1 below:

[0054] Example 1 0.65 16.1% 74.7% 3.2% Example 2 0.58 6.9% 85.1% 3.50% Example 3 0.72 15.5% 77.5% 4.0% Comparative Example 1 1.25 48.0% 32.0% 20.0% Comparative Example 2 0.31 23.0% 58.0% 19.0%

[0055] Table 1. Record of experimental data for characterization using the (DFT model) method in gas adsorption BET.

[0056] Comparing Examples 1-3, it can be seen that all three examples employ a complete three-stage process of foaming, compression, and activation, adjusting only the precursor type, thickening agent system, and activation atmosphere. The final products consistently achieve the core indicators of a total pore volume ≥0.5 cm³ / g, a mesopore volume ratio of 2–10 nm >70%, a micropore (<2 nm) ratio <25%, and a macropore (10–50 nm) ratio <5%. In Example 2, the mesopore rate reaches 85.1%, with pore size highly concentrated in the 2–10 nm range. This result demonstrates that the three-stage control strategy of this invention has good raw material adaptability and can be extended to various carbon precursors such as biochar and resin-based char. It is also compatible with various activation atmospheres such as CO2 and water vapor, exhibiting strong processability and suitability for large-scale production.

[0057] Comparing the examples with Comparative Example 1, it can be seen that Comparative Example 1 omitted the impregnation thickening and secondary carbonization processes, directly activating the foamed matrix. The final total pore volume reached 1.25 cm³ / g, but the microporosity increased to 48%, the mesopore rate to 20%, and the mesopore rate to only 32%, completely deviating from the design goal of high mesopore rate. The main reason is that the foamed carbon matrix itself has an extremely wide pore size distribution, containing a large number of micropores and mesopores. Without the pore wall thickening step, the mesopores cannot achieve pore size convergence through carbon deposition, and a large number of 10-50 nm channels are retained. Simultaneously, the activation process etches new micropores into the carbon matrix, further increasing the micropore ratio. The final pore size distribution exhibits a high-end-low-middle distribution, failing to achieve mesopore enrichment.

[0058] Comparing the comparative examples with Comparative Example 1 demonstrates that step two utilizes the principle of capillary resistance difference: the larger the pore size, the lower the capillary resistance. The liquid thickener preferentially penetrates into large mesopores and some intermediate pores, while micropores are difficult to enter due to their small pore size. After secondary carbonization, carbon deposits on the inner wall of the large mesopores, significantly reducing the pore size of the large mesopores to the intermediate pore range. This radial convergence from the large mesopore end to the intermediate pores is a core and essential step in increasing the proportion of intermediate pores and reducing the proportion of large mesopores.

[0059] Comparing the examples with Comparative Example 2, it can be seen that Comparative Example 2 omitted the mild activation process, retaining only the foaming and impregnation thickening processes. The final total pore volume plummeted to 0.31 cm³ / g, far below the required 0.5 cm³ / g. The microporosity was 23%, the mesoporosity was 58%, and the mesoporous porosity was 19%, both failing to meet the standards for pore volume and pore size distribution. The main reason for this is that during the impregnation thickening process, the carbon precursor deposited on the inner wall of the pores occupies a large amount of pore volume, leading to a significant decrease in total pore volume. Simultaneously, the original <2nm micropores in the substrate could not be directionally etched and enlarged, resulting in a high proportion of micropores that could not be converted into effective mesopores, ultimately leading to a mesopore proportion of less than 60%.

[0060] Comparing the comparative examples with Comparative Example 2 demonstrates that: Step 3 utilizes the reactive principle of differences in pore wall curvature. Micropores have large pore wall curvature and high surface energy, resulting in significantly higher carbon atom reactivity compared to the smooth pore walls of mesopores. Under mild activation conditions, micropores are preferentially vaporized and etched, expanding their pore size to 2–4 nm and transforming into mesopores. Meanwhile, the expansion of mesopores is minimal, achieving radial convergence of pores from the micropore end to mesopores. Simultaneously, the activation etching can compensate for the pore volume loss caused by Step 2, restoring the total pore volume to above 0.5 cm³ / g, thus balancing pore volume and pore size distribution.

[0061] In summary, the experimental data fully verify the effectiveness of the three-stage reverse regulation scheme of the present invention: by combining the principles of capillary selective deposition and curvature selective activation, the performance targets of high total pore volume and high proportion of mesopores are achieved simultaneously without expensive templates and with simple processes. The pore structure of the product is precisely controllable and adaptable to the application needs of multiple fields such as electrochemical energy storage and adsorption separation.

[0062] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A three-stage preparation method for a high-proportion mesoporous disordered porous carbon material, characterized in that, Includes the following steps: Step 1: Preparation of ultra-high pore volume foamed carbon matrix: The carbon precursor powder and chemical foaming agent are mixed evenly at a mass ratio of 100:5-30. The mixture is heated to 600-900℃ under an inert atmosphere for carbonization. After holding at this temperature for 10-120 minutes, it is cooled to obtain a foamed carbon matrix with a total pore volume of 1.5-2.8 cm³ / g. Step 2: Directional pore wall compression and densification: Prepare a liquid carbon precursor solution as a pore wall thickening agent. Impregnate the foamed carbon matrix obtained in Step 1 in the pore wall thickening agent. The impregnation conditions are: impregnation time 1-120 minutes, vacuum degree 0-0.1MPa to allow the thickening agent to penetrate into the macropores and mesopores. After removal, dry in an environment with a drying and curing temperature of 90-150℃. Then, perform secondary carbonization at 1500-1800℃ under an inert atmosphere and keep warm for 0.5-3 hours. After carbonization, the thickening agent is deposited on the inner wall of the pores, reducing the pore size of macropores and mesopores. Step 3: Mild activation and directional pore expansion: The carbonized product obtained in Step 2 is placed in an oxidizing atmosphere and mildly activated at 700-900℃ for 300-650 minutes. After cooling, a high proportion of disordered porous carbon material with mesopores is obtained.

2. The three-stage preparation method according to claim 1, characterized in that, The carbon-containing precursor powder mentioned in step one is selected from one or more of coconut shell charcoal, walnut shell charcoal, urea-formaldehyde resin, phenolic resin, melamine-urea-formaldehyde resin, sucrose, and starch; the chemical foaming agent is selected from one or more of ammonium bicarbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, and urea.

3. The three-stage preparation method according to claim 2, characterized in that, The carbon-containing precursor powder mentioned in step one is biomass fruit shell micro powder with a mesh size of 500-1000 mesh and a water absorption rate of >50%; the chemical foaming agent is potassium bicarbonate, and its addition amount is 10-20% of the mass of the carbon-containing precursor powder.

4. The three-stage preparation method according to claim 1, characterized in that, The heating rate in step one is 2–20 °C / min; the inert atmosphere is one of nitrogen, argon, or helium.

5. The three-stage preparation method according to claim 1, characterized in that, The pore wall thickening agent mentioned in step two is a liquid carbon precursor solution with a mass fraction of 5-35%, wherein the liquid carbon precursor solution is selected from one of the following: sucrose aqueous solution, glucose aqueous solution, furfuryl alcohol ethanol solution, and phenolic resin ethanol solution.

6. The three-stage preparation method according to claim 5, characterized in that, The pore wall thickening agent is a sucrose aqueous solution with a mass fraction of 10-20%.

7. The three-stage preparation method according to claim 1, characterized in that, The impregnation conditions in step two are: impregnation time 20 to 60 minutes, vacuum degree -0.02 to -0.08 MPa.

8. The three-stage preparation method according to claim 1, characterized in that, The oxidizing atmosphere mentioned in step three is one of carbon dioxide, water vapor, or oxygen.

9. The three-stage preparation method according to claim 1, characterized in that, The activation time in step three is 300-500 minutes.

10. A high-proportion, disordered, porous carbon material with mesopores, characterized in that, The porous carbon material prepared by the three-stage preparation method according to any one of claims 1 to 9 has a three-dimensional interconnected disordered pore structure with a total pore volume ≥ 0.5 cm³ / g; based on the pore volume ratio, the proportion of mesopores with a pore size of 2 to 10 nm is > 70%, the proportion of micropores with a pore size of less than 2 nm is < 25%, and the proportion of macropores with a pore size of greater than 10 nm is < 5%.